Surgical Repair of a Superior Sternal Cleft in an Infant - Klein, Tobias; Kellner, Maximilian; Boemers, Thomas Michael; Mack-Detlefsen, Birte (European Journal of Pediatric Surgery Reports, 2015)
Sternal cleft is a rare congenital malformation with little more than 100 cases published worldwide. Incomplete sternal clefting in a female newborn is the most frequent form seen. First-line treatment is the surgical defect closure in the neonatal period. Presurgical examination has to focus on common associated malformations, in particular cardiac defects. The surgical repair of sternal cleft itself shows satisfying functional and cosmetic results with low complication rates. We present the case of a 4-month-old male infant with a superior sternal cleft.
Keywords: sternal cleft; chest wall malformation; infant; pericardial patch